Less-lethal weapons: ocular trauma in Chile as psychosocial trauma. Challenges from a human rights and comprehensive perspective: - Tejada, Jose; Arriaza, Alejandra; Sinclaire, Danae; Vargas, Alejandra (Torture Journal, 2024)
Introduction: In October 2019 in Chile, massive protests broke out in the so-called social uprising. The repressive response of the armed forces of order and security resulted in serious and massive violations of human rights, with between 400 and 500 victims of ocular trauma caused mainly by shots from anti-riot shotguns, constituting the largest number of cases in the world. It is proposed to evaluate the different dimensions of the impact of ocular trauma due to state violence, using the concept of psychosocial trauma and a support model that integrates the medical-psychological and social dimensions. Methods: Human rights violations of the period are described, focusing on cases of ocular trauma, and state and civil society responses. The requests of a survivors’ organisation in truth, justice and reparation is presented. A clinical case of ocular trauma treated in our centre is analyzed. Results: Survivors of ocular trauma manifest post-traumatic reactions regardless of the severity of their ocular injuries. The impact on the mental health of survivors of ocular trauma due to state violence is a phenomenon where the psychic and psychosocial impact of trauma due to socio-political violence intersects with the short- and long-term mental health effects of ocular trauma. Discussion: The impact of sociopolitical trauma must be understood considering the reality of the individual and social subject, considering their cultural, socioeconomic and political reality. Recovery from traumatic psychological injury must be addressed in its medical, sensory rehabilitation, psychological and psychosocial dimensions, including processes of social recognition, search for justice and comprehensive reparation of damage. In contexts of impunity, a model is proposed that integrates rehabilitation with psycho-legal support, promotion of agency and organisation, within the framework of commitment to the movement and principles of human rights.